PASSER HISPANIOLENSIS IS A NEW NESTING SPECIES ON NORTH-WESTERN COAST OF THE CRIMEAN PENINSULA - Sergey Yu. Kostin; Nataliya A. Bagrikova; Nataliya A. Tarina (Юг России: экология, развитие)
Aim. The aim of the research is to study the potential nesting sites of the Spanish sparrow (Passer hispaniolensis) on the northwest coast of Crimea. Methods. Material was compiled during 2016-2018. The generally accepted methods of road and foot route census study were applied. Nesting stations were explored: nests of storks, birds of prey and corvids, forest belts and reed beds. Results. On the basis of research, the presence of Passer hispaniolensis in the north-western Crimea, in particular, within the borders of the Lebyazhy Islands («Swan Islands») specially protected natural area, has been established. It is revealed that for nesting, this species of sparrow prefers the areas close to fields and is not often found in human settlements. During the nesting period, an increase in the number from 15 to 45 pairs was noted. The greatest number of breeding pairs of spanish sparrow is found in the nests of the white stork. Late arriving birds form colonies on trees in close proximity to stork nests. Conclusion. Nesting of Passer hispaniolensis is most likely due to changes in the hydrological regime and land use structure, since rice crop rotation (until 2014) has been replaced by other grain crops (barley, wheat) and tilled crops (sunflower, maize). Thus, at present, the breeding ornithofauna of the protected area is represented by 92 species of birds.